Neighboring Group Participation of Benzoyl Protecting Groups in C3‐ and C6‐Fluorinated Glucose. Issue 15 (13th April 2022) - Greis, Kim; Kirschbaum, Carla; Fittolani, Giulio; Mucha, Eike; Chang, Rayoon; von Helden, Gert; Meijer, Gerard; Delbianco, Martina; Seeberger, Peter H.; Pagel, Kevin
Abstract: Fluorination is a potent method to modulate chemical properties of glycans. Here, we study how C3‐ and C6‐fluorination of glucosyl building blocks influence the structure of the intermediate of the glycosylation reaction, the glycosyl cation. Using a combination of gas‐phase infrared spectroscopy and first‐principles theory, glycosyl cations generated from fluorinated and non‐fluorinated monosaccharides are structurally characterized. The results indicate that neighboring group participation of the C2‐benzoyl protecting group is the dominant structural motif for all building blocks, correlating with the β‐selectivity observed in glycosylation reactions. The infrared signatures indicate that participation of the benzoyl group in enhanced by resonance effects. Participation of remote acyl groups such as Fmoc or benzyl on the other hand is unfavored. The introduction of the less bulky fluorine leads to a change in the conformation of the ring pucker, whereas the structure of the active dioxolenium site remains unchanged. Abstract : The influence of fluorination on the gas‐phase structure of the glycosyl cation is probed with cryogenic infrared spectroscopy. It is shown that for building blocks, readily used in automated‐glycan assembly, C2 benzoyl protecting groups participate and shield the α‐side of the anomeric carbon. This effect is enhanced through resonance stabilization of the positive charge of the phenyl ring in the benzoyl group.